2021
DOI: 10.3390/nu13072164
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Four Weeks Dietary Intervention with 8-Hour Time-Restricted Eating on Body Composition and Cardiometabolic Risk Factors in Young Adults

Abstract: Recently, intermittent fasting, also known as time-restricted eating (TRE), has become a popular diet trend. Compared to animal studies, there have been few studies and inconclusive findings investigating the effects of TRE in humans. In this study, we examined the effects of 8 h TRE on body weight and cardiometabolic risk factors in young adults who were mainly active at night. A total of 33 young adults completed the 8 h TRE for 4 weeks. Body composition was measured by bioelectrical impedance analysis at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Although current available data did not support a stronger effect of TRF on body weight and metabolic improvement as compared to continuous caloric restriction, the mechanistic explanation behind this phenomenon remains raised great interest to researchers. Some controversial issues, including inaccurate recording of food intake, unmonitored energy expenditure and the involvement of physiological adaptation were still need to be determined ( 8 11 , 13 , 14 , 21 24 , 26 , 32 , 33 ). Therefore, we conducted the first rigorous trial to systematically quantify and compare the energy balance during TRF intervention in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Although current available data did not support a stronger effect of TRF on body weight and metabolic improvement as compared to continuous caloric restriction, the mechanistic explanation behind this phenomenon remains raised great interest to researchers. Some controversial issues, including inaccurate recording of food intake, unmonitored energy expenditure and the involvement of physiological adaptation were still need to be determined ( 8 11 , 13 , 14 , 21 24 , 26 , 32 , 33 ). Therefore, we conducted the first rigorous trial to systematically quantify and compare the energy balance during TRF intervention in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] In addition, IF is a new diet that is more flexible, safe, and compliant than traditional calorie restriction diets. [ 27 ] However, few studies have directly compared their weight loss effects and their effects on metabolic disorders and other health indicators in obese patients. Therefore, this study aimed to investigate the effects of 3 different dietary interventions (CRD, HPD, and IF) on body weight, BMI, body fat, glucose, and lipid metabolism, to provide a reference for overweight/obese people to choose appropriate methods.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, when energy restriction in the intermittent fasting group was equivalent with baseline intake or to comparison/control group, weight loss either did not occur or did not differ from the comparison group 27,30,31,37,51,62,67,69,73 . Lack of reporting or inadequate reporting of energy balance, however, is one of the predominant problems across mADF, cADF and TRE interventions 6,8,10,11,13–15,19,25,26,29,60,65,66,68 …”
Section: Time Of Eating Interventions In Individuals Without Establis...mentioning
confidence: 99%
“…Intermittent fasting and other interventions to target time of eating have emerged as a proposed therapy to induce weight loss 6‐21,22 and improve cardiometabolic risk factors, such as body composition, 7,8,12,14,15,22,23,24 blood pressure, 7,10,12,23,25‐27 glycaemia, 13,20,25 and lipids, 7,12,20 and some improvements may even be independent of weight loss 28 . Recent randomized controlled trials, however, have been unable to confirm the favourable results shown in preclinical work and single‐arm trials of intermittent fasting 29‐31 .…”
Section: Introductionmentioning
confidence: 99%